Do financial markets reward government spending efficiency? - Afonso, António (2021)
We link governments’ spending efficiency scores, to sovereign debt assessments made by financial markets´, more specifically by three rating agencies (Standard & Poors, Moody´s and Fitch). Public efficiency scores are computed via data envelopment analysis. Then, we rely notably on ordered response models to estimate the response of sovereign ratings to changes in efficiency scores. Covering 34 OECD countries over the period 2007-2018, we find that increased public spending efficiency is rewarded by financial markets via higher sovereign debt ratings. In addition, higher inflation and government indebtedness lead to sovereign rating downgrades, while higher foreign reserves contribute to rating upgrades.